El realismo político y las relaciones internacionales: : Un enfoque para entender los conflictos internacionales - Quispe Pari, César Alberto (2023)
In the study of International Relations it is necessary to understand the role that Political Realism has played throughout the 20th century, for the study of the international panorama under an objective and systematic criterion of the action of States as well as political leaders or drivers. In that sense, Political Realism has been the tradition and theoretical approach that has provided greater success in understanding the rise and fall of power between States in the international arena, as well as the balance of power, the formation of alliances, conflicts and competitions between countries and blocks of countries, as well as arms races and wars between powers of global reach.